PENGARUH PENGETAHUAN PRODUK DAN KONTEN PEMASARAN MEDIA SOSIAL TIKTOK TERHADAP KESADARAN MEREK: Survei Pada Brand Lokal Kosmetik Koola - Khairina Nadhilah (2023)
Content marketing is a marketing technique that is very common for us to find on social media and has become a trend nowadays. Based on the enthusiasm of Indonesian women for lip cosmetic products and the rise of content marketing techniques by beauty business people, this study tries to discuss how content marketing influences brand awareness which is mediated by product knowledge by consumers or the target market itself. @koolacreation is a lip cosmetic product that utilizes content marketing to popularize its products, and strives to achieve the highest level of brand awareness. This study used a quantitative explanatory approach with a survey method by distributing questionnaires to 100 respondents with certain criteria that had been formulated by the researcher. The theory used in this study is Cognitive Response Theory by Anthony G. Greenwald [1986] which studies human cognitive responses to persuasive messages and changes in attitudes. The conclusion from the results obtained for this study is that content marketing by mediating product knowledge can influence brand awareness with a percentage of 27%.